The dyadic effects of HIV stigma on the mental health of children and their parents in South Africa - Gamarel, K; Kuo, C; Boyes, M; Cluver, L (Taylor and Francis, 2017)
HIV stigma—both “self-stigma” toward positive individuals and “stigma by association” toward their families—is linked with adverse mental health. This study examined how stigma was associated with the mental health of parents and children in South Africa. Parent-child dyads (n = 2,477 dyads) in South Africa participated in a cross-sectional survey. For both parents and children, greater stigma was associated with their own reports of greater anxious and depressive symptoms. Parents’ reports of stigma were associated with children’s greater anxious and depressive symptoms. Children’s reports of stigma were related to parents’ greater anxious and depressive symptoms. There was a significant interaction, such that the association between parent stigma and depression was stronger when children also reported high levels of stigma. Findings provided support the effect of HIV stigma on the mental health of families and illustrate the importance of taking a family-based approach to stigma-reduction interventions to alleviate mental health problems.